GIS Based Morphometric Analysis of Bori-Chikli Watershed of Jalgaon District, Maharashtra, India: GIS Based Morphometric Analysis of Bori-Chikli Watershed of Jalgaon District, Maharashtra, India - Sujit S. Shimpi; V. M. Rokade (International Journal of Economic and Environmental Geology, 2017)
Water is a very important asset for life on the earth. Because of an increasing demand, groundwater exploration and exploitation needs detailed geo-scientific investigations. GIS and remote sensing are an advent technology useful in drainage morphometric studies. In present investigation, authors studied morphometry of the drainage systems. Geologically, area is composed of alluvium, massive and/or fractured and weathered basaltic flows (simple and compound) and small patches of sand gravel and silt along major streams with E-W, NW-SE and N-S trending dykes. Morphometric analysis explains the geometry of drainage basin, drainage network, texture and relief characteristics. The study area shows dendritic drainage pattern, associated in areas having similar lithology and low relief. Present research paper shows morphometric analysis of drainage basin using high-resolution remote sensing data and GIS tool to evaluate various parameters for watershed development and management plan in Bori-Chikli watershed of the Jalgaon district, Maharashtra state. Keywords: Morphometric analysis, Bori-Chikli watershed, Maharashtra, India.